Cynomorium songaricum Extract Alleviates Memory Impairment through Increasing CREB/BDNF via Suppression of p38MAPK/ERK Pathway in Ovariectomized Rats. (23rd May 2019) - Tian, Fang-ze; Chang, Hong-sheng; Liu, Jian-xun; Zheng, Junchao; Cheng, Dan; Lu, Yi
Abstract : Cynomorium songaricum Rupr is a very important traditional Chinese medicine for tonifying the kidney, which has a significant effect on improving estrogen level on the long term. In many studies, it can improve the learning and memory function of ovariectomized (OVX) model animals . 10 of the 50 rats received only bilateral back surgery and were harvested with the same amount of fat as the ovaries without removing the ovaries as sham group; remains underwent bilateral ovariectomy and equally randomized into five groups: sham group, with OVX as model group, estradiol valerate (EV, 0.2 mg/kg) as positive control, with 3.3 and 33 mg/kg body weight/day of ethyl acetate extract of Cynomorium songaricum extract (CSE) as low and high dosage groups, respectively. The orally administered CSE to ovariectomized rats exerted an ameliorative effect on learning and memory in the Morris water maze tests. All rats were sacrificed after 8 weeks of treatment, and tissue was analyzed using histopathology and electron microscopy. To comprehensively examine the mechanism, brain derived neurotrophic factor (BDNF), p-p38 mitogen-activated protein kinase (p-p38MAPK), extracellular regulated protein kinases (ERK), p-extracellular regulated protein kinases (p-ERK), and p-cAMP-response element binding protein (p-CREB) were detected by Western blotting. Using histopathology and electron microscopy, it was clearly observed that the pyramidal neurons of the hippocampal CA1 area were reduced in the OVX groups, indicating that CSE could attenuate the loss of pyramidal neurons in hippocampal CA1 and revert the synaptic morphological variations produced by ovariectomy. Mechanistically, the expressions of p-p38MAPK and p-ERK levels were significantly downregulated by CSE intervention, whereas the BDNF and p-CREB were significantly upregulated by CSE as compared to the control. Concisely, Cynomorium songaricum Rupr exhibited potential therapeutic effect on Neuroprotection of ovariectomized rats, and its effect was possibly exerted by p-CREB/BDNF mediated down regulation of ERK/p38MAPK.